A felvidéki gazdaság felzárkózási esélyei a vámunió korában : 1850-1914 - Kaposi, Zoltán (Közép-Európai Közlemények, 2010)
The author was looking for the answer what was the rate of economic development of Upper-Hungary 1867–1914. In the Habsburg Monarch a custom union was instituted between Austria and Hungary in 1850 which made the flow of the factors of production easier. The economy of Upper-Hungary went through a quick transformation in this new economical system. By 1914 it became the most industrialized part of Hungary (beside Budapest) and it had extensive domestic market relations. This quick development had different reasons. The wide social background of the local entrepreneurs (aristocrats, artisans and foreign investors) and the increased demand for the industrial products of Upper-Hungary played an important role in this development. The modern manufacturing system was built in that period. Serious changes happened due to the state industrial support and also the procreation of the credit and railway system. Te author proves that comparing with other parts of Hungary the arrears of the north peripheral areas was significantly lessened by this economical growth.